Penyuluhan penyakit diare pada masyarakat di desa Gunugsari Kecamatan Gunungsari Lombok Barat - Bahjatun Nadrati; Zurriyatun Thoyibah; Zuhratul Hajri; Baiq Ruli Fatmawati; Melati Inayati Albayani; Marthilda Suprayitna; Kurniati Prihatin; Lalu Dedy Supriatna (JOURNAL OF Public Health Concerns, 2021)
Diarrhea is an infectious disease that causes death in infants and toddlers. Diarrhea is currently still a difficult problem to solve in tropical countries like Indonesia. Diarrhea in children is the major cause of death and morbidity in children in the world. The primary cause is contaminating food and water sources. The purpose of counseling is to increase public knowledge about the dangers of diarrhea, its causes, signs, how to prevent it and how to handle it. Participants who attended were 5 peoples involve of men and women. There are limited places for counseling related to the Covid-19 pandemic, which must adjust health protocols. The media used in this counseling were flip charts and leaflets. The results can improve their knowledge about diarrhea. Suggestion; health education program by the health team from the local Public health centre deliveries sustainably with the achievements of the community and still follow health protocols during the Covid-19 pandemic. Keywords: Diarrhea; Community; Health counseling; Health promotion Diare merupakan penyakit infeksi yang menyebabkan kematian pada bayi dan balita. Diare saat ini masih menjadi masalah yang sulit diatasi di negara tropis seperti Indonesia. Diare pada anak merupakan penyebab utama kematian pada anak di dunia. Penyebab utamanya adalah sumber makanan dan air yang tercemar. Tujuan penyuluhan adalah untuk meningkatkan pengetahuan masyarakat tentang bahaya diare, penyebabnya, tanda-tandanya, cara pencegahannya dan cara menanganinya. Peserta yang hadir sebanyak 5 orang melibatkan laki-laki dan perempuan. Tempat konseling masih dibatasi terkait pandemi Covid-19, yang harus menyesuaikan protokol kesehatan. Media yang digunakan dalam penyuluhan ini adalah flip chart dan leaflet. Hasilnya dapat meningkatkan pengetahuan mereka tentang diare. Saran; program penyuluhan kesehatan oleh tim kesehatan dari puskesmas setempat supaya disampaikan secara berkelanjutan dan tetap mengikuti protokol kesehatan selama pandemi Covid-19.